2013
DOI: 10.2190/de.43.1.b
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models of Alcohol Use Based on Attitudes and Individual Values

Abstract: Two predictive models are developed in this article: the first is designed to predict people's attitudes to alcoholic drinks, while the second sets out to predict the use of alcohol in relation to selected individual values. University students (N = 1,500) were recruited through stratified sampling based on sex and academic discipline. The questionnaire used obtained information on participants' alcohol use, attitudes and personal values. The results show that the attitudes model correctly classifies 76.3% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Further research also highlights that individuals with alcohol misuse rarely seek treatment (Cunningham and Breslin, 2004) and this may be attributed to difficulties in accessing care, reluctance to do so due to social stigmas, and even failure of clinicians to accurately identify the early signs of problem behaviors (Drummond et al., 2004). These barriers to screening individuals for alcohol misuse challenge researchers and public health professionals to shift the emphasis from problem-focused screenings to more preventive methods through the creation of predictive models based on the analysis of collateral data, such as survey data on other individual characteristics (e.g., Kumari et al., 2018; García del Castillo Rodríguez et al., 2013; Rosenström et al., 2018) and features of individual activity on social media (e.g., Kosinski et al., 2013; Moreno et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further research also highlights that individuals with alcohol misuse rarely seek treatment (Cunningham and Breslin, 2004) and this may be attributed to difficulties in accessing care, reluctance to do so due to social stigmas, and even failure of clinicians to accurately identify the early signs of problem behaviors (Drummond et al., 2004). These barriers to screening individuals for alcohol misuse challenge researchers and public health professionals to shift the emphasis from problem-focused screenings to more preventive methods through the creation of predictive models based on the analysis of collateral data, such as survey data on other individual characteristics (e.g., Kumari et al., 2018; García del Castillo Rodríguez et al., 2013; Rosenström et al., 2018) and features of individual activity on social media (e.g., Kosinski et al., 2013; Moreno et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that specifically target alcohol consumption found that values of openness to change and self-enhancement favor alcohol use, while conservation and self-transcendence values are associated with lower consumption [22,23]. In terms of the basic values, achievement and hedonism are associated with higher consumption and universalism, tradition, and conformity with lower alcohol use [24].…”
Section: Introductionmentioning
confidence: 99%